2015
DOI: 10.1007/s12195-015-0415-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent and Incremental Cyclic Stretch on ERK Signaling and Collagen Production in Engineered Tissue

Abstract: Intermittent cyclic stretching and incrementally increasing strain amplitude cyclic stretching were explored to overcome the reported adaptation of fibroblasts in response to constant amplitude cyclic stretching, with the goals of accelerating collagen production and understanding the underlying cell signaling. The effects of constant amplitude, intermittent, and incremental cyclic stretching regimens were investigated for dermal fibroblasts entrapped in a fibrin gel by monitoring the extracellular signal-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In order to subject fibroblasts to biochemical stimuli and stretch while simulating myocardial architecture and material properties, we employed a previously developed strategy in which cells are incorporated into a fibrin matrix and seeded into culture wells containing vertical, opposing sets of silicone posts. Fibroblasts cultured in this manner have been shown to remodel the surrounding matrix and form aligned constructs with comparable stiffness to myocardial levels [11,12,32,33], thus mimicking in vivo mechanical conditions more closely than 2-dimensional mechanical testing systems.. Although mCFs assumed an activated state throughout treatment, likely due to prior culture with stiff tissue culture flasks, the use of soft gels prevented further stiffness-related stimulation during treatment, and myofibroblast-mediated remodeling could be examined without confounding mechanical factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to subject fibroblasts to biochemical stimuli and stretch while simulating myocardial architecture and material properties, we employed a previously developed strategy in which cells are incorporated into a fibrin matrix and seeded into culture wells containing vertical, opposing sets of silicone posts. Fibroblasts cultured in this manner have been shown to remodel the surrounding matrix and form aligned constructs with comparable stiffness to myocardial levels [11,12,32,33], thus mimicking in vivo mechanical conditions more closely than 2-dimensional mechanical testing systems.. Although mCFs assumed an activated state throughout treatment, likely due to prior culture with stiff tissue culture flasks, the use of soft gels prevented further stiffness-related stimulation during treatment, and myofibroblast-mediated remodeling could be examined without confounding mechanical factors.…”
Section: Methodsmentioning
confidence: 99%
“…We additionally tested the hypothesis that stretch can not only act alongside biochemical stimuli but also alter cellular responses to these stimuli, as previous studies have demonstrated similar signaling mechanisms in both chemo-and mechano-transduction, such as mitogenactivated protein kinase and Akt signaling pathways [32,[45][46][47]. We found that stretch altered fibroblast sensitivity towards agonists by either sensitizing cells towards agonists that suppress protease expression (e.g.…”
Section: Stretch-dependent Sensitivity To Biochemical Stimulationmentioning
confidence: 96%
“…Further studies on human dermal fibroblasts were conducted by exposing the cells to tension forces (Table 17.4). The most evident result after the application of tensile forces on fibroblasts loaded in flexible silicon membranes was the increased production of ECM synthesis mediators [133] and of ECM proteins, especially collagen and elastin [17][18][19][20][21][22][23][24][133][134][135][136][137][138]. Moreover, collagen fibrils [134,136,137,139,140] were aligned in agreement with the alignment of the cells but perpendicular to the stretch [137,[139][140][141].…”
Section: Effect Of Forces Over Fibroblasts and Keratinocytesmentioning
confidence: 99%
“…All these results suggest that fibroblasts present a more active "synthetic" phenotype that coincides with myofibroblast phenotype as shown by the expression of α-SMA [19,135,145,146]. These mechanotransduced responses are mediated by different signaling pathways and mediators, including integrin β1 [24,137,141], focal adhesion kinase [141], Rho GTPases [141], TGF-β pathway [24,133,135,137,147], p38 pathway [21,135,141,148], ERK pathway [18,21,135,148], Jnk pathway [18], Akt pathway [18,148], Wnt pathway [140], SMAD [147], and P130cas [24,137]. Nevertheless, in some studies, tension was found to decrease fibroblast proliferation [20,148], collagen production [20,149], and the release of CTFG [149,150].…”
Section: Effect Of Forces Over Fibroblasts and Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation